Content Vs. Learning: An Old Dichotomy in Science Courses - Bergtrom, Gerald (Online Learning, 2011)
The principles of course redesign that were applied to a gateway Cell Biology course at the University of Wisconsin-Milwaukee are applicable to courses large and small, and to institutions of any size. The challenge was to design a content-rich science course that kept pace with present and future content and at the same time use principles of active learning to model how science is done, from deduction and inference to the articulation and testing of hypotheses and the interpretation of experimental data. Redesign began with a recognition that active learners achieve deeper understanding that passive learners. Key features of the resulting blended course include (a) online delivery of all basic content; (b) greater responsibility of students for their own learning; (c) student-centered activities with specific learning objectives; (d) a new balance of summative and low- stakes progressive assessment of student achievement of learning objectives. In the final version of the blended course, there are no F2F lectures. Freed from the anxieties of content coverage, the instructor facilitates student engagement with content and with each other in assessed activities that support broadly defined essential learning outcomes. Samples of integrated online and F2F interactive, collaborative learning activities are included with preliminary data indicating a positive impact of blended learning in Cell Biology.